2005
DOI: 10.1021/es0491681
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Polycyclic Aromatic Hydrocarbon Compounds in Groundwater Using Poplar Trees

Abstract: A seven-year study was conducted to assess the effectiveness of hybrid poplar trees to remediate polycyclic aromatic hydrocarbon (PAH) compounds in soil and groundwater at a creosote-contaminated site. A reduction in the areal extent of the PAH plume was observed in the upper half of the 2-m-thick saturated zone, and PAH concentration levels in the groundwater declined throughout the plume. PAH concentrations began to decline during the period between the third and fourth growing seasons, which coincided with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…Generally, the rhizosphere of plants harbours a higher diversity of bacteria than the surrounding bulk soil due to root exudates and oxygen that stimulate bacteria (Briones et al, 2003). Most interest in phytoremediation with woody plants has been devoted to Populus (Spriggs et al, 2005;Widdowson et al, 2005;Zalesny et al, 2005) and Salix (Vervaeke et al, 2003) with the aim to combat heavy metal pollution. Not much attention has been devoted to elucidate applicability of woody plants for remediation of organic pollution (Tesar et al, 2002;Mueller and Shann, 2006;Palmroth et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the rhizosphere of plants harbours a higher diversity of bacteria than the surrounding bulk soil due to root exudates and oxygen that stimulate bacteria (Briones et al, 2003). Most interest in phytoremediation with woody plants has been devoted to Populus (Spriggs et al, 2005;Widdowson et al, 2005;Zalesny et al, 2005) and Salix (Vervaeke et al, 2003) with the aim to combat heavy metal pollution. Not much attention has been devoted to elucidate applicability of woody plants for remediation of organic pollution (Tesar et al, 2002;Mueller and Shann, 2006;Palmroth et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their carcinogenicity, mutagenicity, and toxicity, PAHs are listed as priority toxic pollutants by the United States Environmental Protection Agency (10). Acenaphthylene, one of the listed PAHs, is found as a constituent of coal tar and tobacco smoke (15) and of organic contaminants in groundwater (31). This compound is well-known for causing adverse effects in humans as well as aquatic organisms (14).…”
mentioning
confidence: 99%
“…Naphthalene is the primary contaminant volatilized into pore air and dissolved into groundwater from the creosote, which is present as a dense nonaqueous phase liquid (DNAPL) in the surficial aquifer. Previous studies at the site demonstrated that naphthalene undergoes preferential remediation over the PAHs with three or more rings and enhanced biodegradation is occurring in areas impacted by poplar trees (1,2). Direct volatilization of naphthalene to the atmosphere was measured at the site and found to be enhanced by the presence of the phytoremediation system because the trees reduce the saturated thickness separating the submerged DNAPL and the water table and thus enhance vertical fluxes of contaminants (3).…”
Section: Introductionmentioning
confidence: 89%
“…Phytoremediation of polycyclic aromatic hydrocarbon (PAHs) compounds using poplar trees has been studied for a period of 7 years at a creosote-contaminated site in north-central Tennessee (1). Naphthalene is the primary contaminant volatilized into pore air and dissolved into groundwater from the creosote, which is present as a dense nonaqueous phase liquid (DNAPL) in the surficial aquifer.…”
Section: Introductionmentioning
confidence: 99%